2021
DOI: 10.3390/f12010093
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ecology of Forest, Heath, and Shrub Savannah Alternate States in Eastern Canada

Abstract: In eastern Canada, alternation of wildfire regime due to fire suppression creates alternate vegetation states converting black spruce forest to heath and shrub savannah (SS). We compared the taxonomic diversity (TD) and functional diversity (FD) of post-fire forest, heath, and SS alternate states to determine if community FD can explain their persistence. We hypothesized that (i) species diversity (TD and FD) would be the highest in forest followed by SS and heath due to decreased interspecific competition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The diversity of plant functional traits, as measured by FDis, is a measure of the diversity of plant functional traits within a community, and it is an important indicator of ecosystem health and resilience in rangeland management (St. James & Mallik, 2021). We found that high grazing intensity had a negative effect on functional dispersion, as also found in Chillo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of plant functional traits, as measured by FDis, is a measure of the diversity of plant functional traits within a community, and it is an important indicator of ecosystem health and resilience in rangeland management (St. James & Mallik, 2021). We found that high grazing intensity had a negative effect on functional dispersion, as also found in Chillo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the significance of maintaining plant functional diversity for ecosystem functioning has gained increasing recognition in recent years (Hagan et al., 2023; Osborne et al., 2018). Here, specific plant functional traits have been identified as crucial indicators of ecosystem functioning in the face of unpredictable disturbances (Osborne et al., 2018; St. James & Mallik, 2021).…”
Section: Introductionmentioning
confidence: 99%